Evaluation of Waiting Time for Non-Concoction Electronic Prescriptions for Patients at The Outpatient Pharmacy Installation of Tasik Medika Citratama Hospital, Tasikmalaya City - Fauzi, Muhammad Imam; Ramdan, Susan Sintia; Purwati, Ita (Ad-Dawaa : Journal of Pharmacy, 2025)
The waiting time is one of the minimum standards for pharmaceutical services in hospitals, the waiting time for non-concocted drug services is the grace period from the time the patient submits the prescription to the time of receiving the non-concocted drug with the minimum standard set by the Ministry of Health, which is less than 30 minutes. The aim of this study is to determine the suitability of the waiting time for outpatient non-compound electronic prescription services at the Pharmacy Installation of Tasik Medika Citratama Hospital with the minimum standards stipulated in the Decree of the Minister of Health No. 129 of 2008 concerning Minimum Hospital Service Standards. This study is a prospective observational study using the Probability Sampling method by taking samples using quote sampling according to the inclusion criteria. The data taken were 260 non-compound electronic prescriptions. The average waiting time for non-compound electronic prescription services was 25.19 minutes. This meets the Minimum Hospital Service Standards according to the Decree of the Minister of Health No. 129 of 2008.